Uptake of Biosimilars and Its Economic Implication for the Treatment of Patients with Rheumatoid Arthritis in Korea - Cho, Soo-Kyung; Jung, Sun-Young; Kim, Hyoungyoung; Song, Yeo-Jin; Lee, Kyungeun; Sung, Yoon-Kyoung (Journal of Korean medical science, 2021)
We aimed to examine the uptake of infliximab and etanercept biosimilars in patients with rheumatoid arthritis (RA) and its economic implication for healthcare expenditure.BACKGROUNDWe aimed to examine the uptake of infliximab and etanercept biosimilars in patients with rheumatoid arthritis (RA) and its economic implication for healthcare expenditure.Using Korean Health Insurance Review and Assessment Service National Patient Samples, we extracted RA patients who used biologic disease modifying anti-rheumatic drugs (bDMARDs) between 2009 and 2018. Descriptive statistics were used to explain the basic features of the data. We calculated the proportion of users of each bDMARD among total patients with bDMARDs half-yearly. We assessed changes in the utilization proportions of bDMARDs including 4 tumor necrosis factor inhibitors (TNFis) and 2 non-TNFis, which have been approved for RA in Korea: etanercept, infliximab, adalimumab, golimumab, tocilizumab, and abatacept, and analyzed the changes in market share of biosimilars among the bDMARDs after their introduction. Overall trends of medical costs for each bDMARD were presented over the 10-year period.METHODSUsing Korean Health Insurance Review and Assessment Service National Patient Samples, we extracted RA patients who used biologic disease modifying anti-rheumatic drugs (bDMARDs) between 2009 and 2018. Descriptive statistics were used to explain the basic features of the data. We calculated the proportion of users of each bDMARD among total patients with bDMARDs half-yearly. We assessed changes in the utilization proportions of bDMARDs including 4 tumor necrosis factor inhibitors (TNFis) and 2 non-TNFis, which have been approved for RA in Korea: etanercept, infliximab, adalimumab, golimumab, tocilizumab, and abatacept, and analyzed the changes in market share of biosimilars among the bDMARDs after their introduction. Overall trends of medical costs for each bDMARD were presented over the 10-year period.Since the introduction of the biosimilar TNFis in 2012, the proportion of their use among bDMARDs steadily increased to 15.8% in 2018. While there has been a gradual increase in the use of biosimilar TNFis, the use of the corresponding originators has been decreasing. The introduction of biosimilar TNFis has resulted in a decrease in the medical costs of patients using either originator or biosimilar TNFis.RESULTSSince the introduction of the biosimilar TNFis in 2012, the proportion of their use among bDMARDs steadily increased to 15.8% in 2018. While there has been a gradual increase in the use of biosimilar TNFis, the use of the corresponding originators has been decreasing. The introduction of biosimilar TNFis has resulted in a decrease in the medical costs of patients using either originator or biosimilar TNFis.In Korea, the proportional use of biosimilar TNFis has gradually increased since their introduction. The availability of less expensive biosimilar TNFis seems to have brought about a decrease in the medical costs of users of the originators.CONCLUSIONIn Korea, the proportional use of biosimilar TNFis has gradually increased since their introduction. The availability of less expensive biosimilar TNFis seems to have brought about a decrease in the medical costs of users of the originators.